Genome-wide meta-analysis identifies novel loci associated with parathyroid hormone level - Matana, Antonela; Brdar, Dubravka; Torlak, Vesela; Boutin, Thibaud; Popović, Marijana; Gunjača, Ivana; Kolčić, Ivana; Boraska Perica, Vesna; Punda, Ante; Polašek, Ozren; Barbalić, Maja; Hayward, Caroline; et al. (Molecular medicine (Cambridge, Mass.), 2018)
Background Parathyroid hormone (PTH) is one of the principal regulators of calcium homeostasis. Although serum PTH level is mostly accounted by genetic factors, genetic background underlying PTH level is insufficiently known . Therefore, the aim of this study was to identify novel genetic variants associated with PTH levels. Methods We performed GWAS meta-analysis within two genetically isolated Croatian populations followed by replication analysis in a Croatian mainland population and we also combined results across all three analyzed populations. The analyses included 2596 individuals. A total of 7,411,206 variants, imputed using the 1000 Genomes reference panel, were analysed for the association. In addition, a sex-specific GWAS meta-analyses were performed. Results Polymorphisms with the lowest P -values were located on chromosome 4 approximately 84 kb of the 5′ of RASGEF1B gene. The most significant SNP was rs11099476 ( P = 1.15 × 10 −8 ). Sex-specific analysis identified genome-wide significant association of the variant rs77178854, located within DPP10 gene in females only ( P = 2.21 × 10 − 9 ). There were no genome-wide significant findings in the meta-analysis of males. Conclusions We identified two biologically plausible novel loci associated with PTH levels, providing us with further insights into the genetics of this complex trait.